Penerapan Metode Naïve Bayes Classification dalam Analisis Tingkat Pemahaman Siswa Terhadap Guru pada Mata Pelajaran Matematika - Sovia Umbu; Andreas Ariyanto Rangga; Alexander Adis (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
For students, Dasar Elementary School offers a formal education pathway. Mengubah pemahaman siswa terhadap materi pembelajaran is quite important in the learning process. Perlu dicapainya, siswa atau didik adalah fungsi dari adanya seorang pendidik.This is due to the fact that in the process of teaching mathematics, understanding concepts is a foundation that is extremely important for making decisions on the solution of mathematical problems as well as daily problems. Due to a few factors that make it difficult for students to understand math lessons, they find it difficult to understand or even understand them at all. To achieve the maximum learning outcomes, education must be provided by qualified teachers. One of the most important educational resources for achieving the highest learning outcomes is a teacher. A teacher is one of the most important educational resources; learning will be more enjoyable if the teacher can implement a flexible learning model. In addition, teachers are expected to be constantly creative in their approach to teaching. Due to this, a system is required to determine the student's level of proficiency in comparison to the advanced learning environment in order to assess student learning. The collected data from the survey will be divided into two categories: training data and testing data. The model's training data results will be used to assess the accuracy of the data testing. The classification results indicate that the Naïve Bayes algorithm is a good choice for reducing student anxiety levels in foreign language learning, with a remarkably high accuracy rate of 95.24%.